Bidirectional neural connectivity between basal temporal and posterior language areas in humans. Issue 4 (April 2015) - Araki, Kunihiko; Terada, Kiyohito; Usui, Keiko; Usui, Naotaka; Araki, Yasukiyo; Baba, Koichi; Matsuda, Kazumi; Tottori, Takayasu; Inoue, Yushi
Highlights Basal temporal language area (BTL) plays an important role to convert visual semantic information into phonological representation. Neural connectivity between BTL and other language areas is not well known, because no study of direct BTL stimulation has been reported. We demonstrated the neural connectivity between BTL and Wernicke's language area by cortico-cortical evoked potential method.